RESPONDING TO STUDENTS’ WRITING: WHY AND HOW? - Joni Alfin; M. Adnan Latief; Utami Widiati (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
EFL students are required to have a good writing skill. Of course, it will take a process; students should practice a lot and teacher should respond students’s work in order to be better. Many studies have investigated the effect of teacher’s feedback on students writing. In general, the finding showed that there was a positive effect of giving feedback on students’s writing; giving feedback on an assignment helps learners reduce their errors on that assignment during the revision process, the accuracy of students who received written feedback in the immediate post-test outperformed those who did not receive feedback, feedback given  by teacher can improve students' writing performance, and so on. In giving feedback, teacher should consider several things in order that the feedback provided gives good result.